Optimization of Employee Certification System UI Using User-Centered Design Model - Shelya Putri Nurhaliza Abdillah; Dian Permata Sari (Dinasti International Journal of Education Management And Social Science, 2025)
A digital-based employee certification system plays a crucial role in ensuring compliance with industry standards while enhancing employee engagement and productivity. However, a less intuitive interface design remains a challenge in its implementation. This study aims to evaluate the usability of an employee certification website using the User-Centered Design (UCD) approach and the System Usability Scale (SUS) to enhance user experience and information accessibility. The research method involved system testing by 30 employee respondents as primary users, with evaluations based on the SUS. The analysis results indicate that the system achieved an average SUS score of 84.8, classified as "Very Good" and "Acceptable," signifying a high level of usability. These findings confirm that UCD-based design can improve user satisfaction and the efficiency of the certification process. However, certain aspects still require optimization, particularly regarding navigation and system feedback to support more effective interaction. The implications of this study include design improvement recommendations to enhance user engagement, accessibility, and overall certification platform effectiveness. Thus, this research contributes to the development of a more inclusive and responsive certification system that better meets user needs, ultimately supporting the achievement of organizational goals more effectively.